Multimodal Exercise Effects in Older Adults Depend on Sleep, Movement Biography, and Habitual Physical Activity: A Randomized Controlled Trial - Vogel, Oliver; Niederer, Daniel; Vogt, Lutz (Frontiers in Aging Neuroscience, 2021)
Background: The promotion of healthy aging is one of the major challenges for healthcare systems in current times. The present study investigates the effects of a standardized physical activity intervention for older adults on cognitive capacity, self-reported health, fear of falls, balance, leg strength and gait under consideration of movement biography, sleep duration, and current activity behavior. Methods: This single-blinded, randomized controlled trial included 49 community-dwelling older adults (36 women; 82.9 ± 4.5 years of age (Mean [M] ± SD); intervention group = 25; control group = 24). Movement biography, sleep duration, cognitive capacity, self-reported health status, and fear of falls were assessed by means of questionnaires. Leg strength, gait, and current activity levels were captured using a pressure plate, accelerometers, and conducting the functional-reach and chair-rising-test. The multicomponent intervention took place twice a week for 45 min and lasted 16 weeks. Sub-cohorts of different sleep duration were formed to distinguish between intervention effects and benefits of healthy sleep durations. Change scores were evaluated in univariate analyses of covariances (ANCOVAs) between groups and sub-cohorts of different sleep duration in both groups. Changes in cognitive capacity, self-reported health, fear of falls, balance, leg strength, and gait were investigated using the respective baseline values, movement biography, and current activity levels as covariates. Analysis was by intention-to-treat (ITT). Results: We found sub-cohort differences in cognitive capacity change scores [F(3,48) = 5.498, p = 0.003, ηp2 = 0.287]. Effects on fear of falls [F(1,48) = 12.961, p = 0.001, ηp2 = 0.240] and balance change scores F(1,48) = 4.521, p = 0.040, ηp2 = (0.099) were modified by the level of current activity. Effects on gait cadence were modified by the movement biography [F(1,48) = 4.545; p = 0.039, ηp2 = 0.100]. Conclusions: Unlike for functional outcomes, our multicomponent intervention in combination with adequate sleep duration appears to provide combinable beneficial effects for cognitive capacity in older adults. Trainability of gait, fear of falls, and flexibility seems to be affected by movement biography and current physical activity levels. Trial registration: This study was registered at the DRKS (German Clinical Trials Register) on November 11, 2020 with the corresponding trial number: DRKS00020472.